(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2018)
In contemplation of the economic troubles faced by the last Labour Government, Tony Benn famously declared that the very scale of crisis was the ’occasion for making the fundamental changes and not (the) excuse for postponing them’ (1989). So it is today. The real economic challenge is how to secure not just short-term economic management again, but long-term fundamental economic change.